Perbandingan Hasil Deteksi Air Tanah Dengan Metode Geolistrik Konfigurasi Schlumberger, Wenner, Wenner-Schlumberger, Dipole-Dipole Dan Pole-Pole - Ashady Adhe; Waterman SB; Nurkhamim (ReTII, 2022)
Water is an essential resource for human being and the needs significantly increases from time to time. The highly demand of water may cause water scarcity. Based on that condition, groundwater exploration is urgently needed, where at least the location and depth of the groundwater can be identified through an accurate method. Geoelectric, on the other hand, is a geophysics method that is commonly used for identifying geology structures, including for groundwater exploration or identification. The objectivity of this research was to compare the geoelectric configuration accuracy, which Schlumberger, Wenner, Wenner-Schlumberger, Dipole-dipole, and Pole-pole were discussed. As a result, configuration of Wenner amd Wenner-Schlumberger showed the best results based on the vertical resolutiuon, the CST, and the sounding parameters.